Outcomes of Patients Treated in the UK Proton Overseas Programme: Central Nervous System Group. Issue 5 (May 2023) - Gaito, S.; Hwang, E.J.; France, A.; Aznar, M.C.; Burnet, N.; Crellin, A.; Holtzman, A.L.; Indelicato, D.J.; Timmerman, B.; Whitfield, G.A.; Smith, E.
Abstract: Aims: In 2008, the UK National Health Service started the Proton Overseas Programme (POP), to provide access for proton beam therapy (PBT) abroad for selected tumour diagnoses while two national centres were being planned. The clinical outcomes for the patient group treated for central nervous system (CNS), base of skull, spinal and paraspinal malignancies are reported here. Materials and methods: Since the start of the POP, an agreement between the National Health Service and UK referring centres ensured outcomes data collection, including overall survival, local tumour control and late toxicity data. Clinical and treatment-related data were extracted from this national patient database. Grade ≥3 late toxicities were reported following Common Terminology Criteria for Adverse Events (CTCAE) v 4.0 definition, occurring later than 90 days since the completion of treatment. Results: Between 2008 and September 2020, 830 patients were treated within the POP for the above listed malignancies. Overall survival data were available for 815 patients and local control data for 726 patients. Toxicity analysis was carried out on 702 patients, with patients excluded due to short follow-up (<90 days) and/or inadequate toxicity data available. After a median follow-up of 3.34 years (0.06–11.58), the overall survival was 91.2%. The local control rate was 85.9% after a median follow-up of 2.81 years (range 0.04–11.58). The overall grade ≥3 late toxicity incidence was 11.97%, after a median follow-up of 1.72 years (0.04–8.45). The median radiotherapy prescription dose was 54 GyRBE (34.8–79.2). Conclusions: The results of this study indicate the safety of PBT for CNS tumours. Preliminary clinical outcomes following PBT for paediatric/teen and young adult and adult CNS tumours treated within the POP are encouraging, which reflects accurate patient selection and treatment quality. The rate of late effects compares favourably with published cohorts. Clinical outcomes from this patient cohort will be compared with those of UK-treated patients since the start of the national PBT service in 2018. Highlights: Providing and building the state of art in radiotherapy in the NHS. The effectiveness of a standardised patient referral pathway. A national prospective registry for PBT. Safety and efficacy of PBT for CNS tumours across the age spectrum. Future toxicity modelling based on robust PBT-derived outcome data.